Restricted insecticide application: a last mile control option for elimination of acute sleeping sickness and progressive control of African animal trypanosomiasis in South-Eastern Uganda - Muhanguzi, D.; Wasswa, A.T.; Abila, P.P.; Mugenyi, A.; Kakuru, M.; Abizera, H.; Ainebyoona, S.; Kansiime, M.; Amanyire, W.; Nkamwesiga, Joseph; Kimuda, P.M.; Rascón-García, K.; et al. (BioMed Central, 2026)
Background: Animal African trypanosomiasis (AAT) poses a significant impediment to livestock production and economic progress in sub-Saharan Africa. To reduce the burden of AAT in Uganda and contribute to the AAT progressive control pathway, there is a need to develop effective AAT and tsetse control measures. In this study, we assessed a combination of chemotherapy and Restricted Insecticide Application Protocol (RAP) as a last mile control option for the progressive control of AAT and acute sleeping sickness in south- eastern Uganda.